EFEKTIVITAS PELATIHAN SELF-REGULATED LEARNING DALAM MENINGKATKAN PRESTASI MATEMATIKA DI MADRASAH TSANAWIAH “X” SLEMAN - Nadia Yumna; Sukarti Sukarti; Uly Gusniarti (JURNAL PSIKOLOGI MALAHAYATI, 2020)
THE EFFECTIVITY OF SELF-REGULATED LEARNING TRAINING TO INCREASE THE STUDENT’S MATHEMATICS ACHIEVEMENT OF MADRASAH TSANAWIYAH “X” SLEMANThis research aimed to determine the effectivity of Self-Regulated Learning training to  increase the student’s mathematics achievement. Subject in this research were 27 student of  class VIII MTs " X " Sleman, which were divided into 14 students as the experimental group and 13 students as the control group. The data was collected using a test of mathematics achievement, mathematic self efficacy scale, interview and observation. The  research design used was pre post control group design. Analysis of the study were  quantitative and qualitative analysis. Quantitative analysis using the Mann-Whitney test to  determine mathematics achievement after the self regulated training given. The  qualitative analysis was done based on observation, interviews and worksheets. The results  of this study shows there was increased mathematics  achievement after training given (Z = -4.189, p < 0.05). The results of this study imply for the importance of developing self regulated learning skills in improving learning achievement Penelitian ini bertujuan untuk mengetahui efektivitas pelatihan Self-Regulated Learning untuk meningkatkan prestasi belajar matematika. Subjek dalam penelitian ini  adalah 27 siswa kelas VIII MTs “X” Sleman, yang dibagi menjadi 14 siswa sebagai kelompok  eksperimen dan 13 siswa sebagai kelompok kontrol. Pengumpulan data dilakukan dengan  menggunakan tes prestasi matematika dan skala efikasi diri matematika, wawancara dan  observasi. Rancangan penelitian yang digunakan adalah pre post control group design. Analisis penelitian yang digunakan adalah analisis kuantitatif dan kualitatif. Analisis kuantitatif  dengan menggunakan uji Mann-Whitney  untuk mengetahui prestasi belajar matematika  siswa setelah diberi pelatihan  Self-Regulated Learning.  Analisis kualitatif dilakukan  berdasarkan observasi, wawancara dan lembar kerja. Hasil penelitian yaitu pada prates dan  pascates prestasi belajar matematika menunjukkan ada peningkatan setelah diberi pelatihan (Z= -4.189, p<0,05). Hasil penelitian ini memberi impilkasi bagi pentingnya pengembangan keterampilan self regulated learning dalam meningkatkan prestasi belajar.